Children at the Mutoscope - Streible, Dan (Cinémas, 2003)
AbstractBy the late 1890s, mutoscopes were associated with “adult” material. Yet such displays were often accessible to children. Two sources of documentation, an 1899 Hearst newspaper campaign against “picture galleries of hell” and U.S. Farm Security Administration photographs of the 1930s, demonstrate the longevity of American children’s access to mutoscopes. The rhetoric of moral panic used in the Hearst campaign was short-lived and self-interested, but instructive in demonstrating how discourse on new media displays a similarly anxious tenor throughout the twentieth century. By contrast, the FSA photographs reveal that the perceived indecencies of the mutoscope were consigned to the margins by the 1930s.